La liberación comercial del maíz y sus márgenes legales de renegociación en el Tratado de Libre Comercio de América del Norte - Rodríguez Rivera, Magdalena (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
This thesis will analyze the existing legal frameworks within which it is possible to realize a renegotiation of the corn trade agreement that currently exists between Mexico and the United States. The legal arguments are based both on existing Mexican law and the mechanisms available through the North American Free Trade Agreement (NAFTA). The need to renegotiate such an agreement is given legal legitimacy due to the fact that Mexico, as a developing country, is subject to special and differential treatment as granted both in the General Agreement and Tariffs and Trade (GATT) and in the right to restrict agricultural imports established in NAFTA. This analysis will clearly highlight why corn should be considered a priority for the Mexican State, and consequently, why the government should establish an agricultural policy directed toward maintaining and encouraging greater self-sufficiency in the production of white corn. This is because white corn is the most fundamental element of the Mexican diet, the most basic crop produced in rural agricultural communities, and corn production represents two- thirds of all agricultural employment in Mexico and 25% of total employment in the country. More than 3 million producers earn their living by growing corn, and if one includes the average rural family as also being dependent on this income, there are more than 18 million4 people who depend on corn production for their livelihood. If the renegotiation of the corn agreement between Mexico and the United States, along with the parallel development of a state policy designed to protect and strengthen the domestic production of white corn are not implemented, Mexico will continue to be an “under-developed” country while millions of people will become unemployed.

En el presente trabajo de tesis se analizan los márgenes legales que guarda el Tratado de Libre Comercio de América del Norte (TLCAN), para llevar a cabo una renegociación del acuerdo maicero entre México y Estados Unidos; desde la legitimidad jurídica que mantiene México como país en desarrollo a efecto de obtener el trato especial y diferenciado que le es otorgado por el Acuerdo General sobre Aranceles Aduaneros y Comercio (GATT siglas en inglés), y los derechos que se desprenden del TLCAN para los efectos de restringir las importaciones de productos agrícolas. En una primera parte, se trata de fundamentar porque el maíz debe considerarse como un asunto prioritario para el Estado, para lo cual debe mantener programas de política agrícola a fin de mantener e incrementar su autosuficiencia alimentaria del maíz blanco; ya que ese grano constituye el eje central en la alimentación del pueblo mexicano, además de ser el cultivo básico en la agricultura campesina, ya que el sector rural en México ocupa el 30% de la población económicamente activa, y la actividad maicera ocupa las dos terceras partes de esa población. Lo cual significa el medio de vida no solamente de los productores sino de sus familias, que considerando el tamaño y promedio de los hogares rurales, son hasta unas 18 millones3 de personas que dependen de la producción de maíz para ganarse la vida en México, y precisamente eso es lo que lo hace ser un país en desarrollo y que aún se agravará esa condición de país en vías de desarrollo, enviando a esa población activa a un desempleo seguro.
Instituto de Investigaciones Económicas y Empresariales. Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2006-0002; TLCAN; Política comercial; Sector agrícola; Importación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/899